2011
DOI: 10.1016/j.ajpath.2010.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution and Phenotype of Decidual Macrophages in Preeclamptic versus Control Pregnancies

Abstract: Maternal immune tolerance of the semiallogeneic fetus is a complex phenomenon. Macrophages are an abundant cell population in the human decidua, and changes in distribution or phenotype may be involved in the development of preeclampsia. The aim of this study was to assess the distribution and phenotype of macrophages in preterm preeclamptic, preterm control, and term control placentas. Placentas of preterm preeclamptic (n ‫؍‬ 6), preterm control (n ‫؍‬ 5), and term control pregnancies (n ‫؍‬ 6) were sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
128
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 36 publications
10
128
1
Order By: Relevance
“…All cases of pre-eclampsia (20/20) were infected with a high-risk HPV type. Our findings support the proposal that HPV infection contributes to the pathogenesis of pre-eclampsia, [37][38][39] and alters overall inflammatory marker expression in pregnancy. 40,41 In a cell culture setting, HPV infection impairs trophoblast cell function by inducing trophoblast cell death and defective endometrial cell recognition.…”
Section: Discussionsupporting
confidence: 90%
“…All cases of pre-eclampsia (20/20) were infected with a high-risk HPV type. Our findings support the proposal that HPV infection contributes to the pathogenesis of pre-eclampsia, [37][38][39] and alters overall inflammatory marker expression in pregnancy. 40,41 In a cell culture setting, HPV infection impairs trophoblast cell function by inducing trophoblast cell death and defective endometrial cell recognition.…”
Section: Discussionsupporting
confidence: 90%
“…M2 macrophage numbers in relation to total macrophages (CD163/CD14 ratio) were lower in placentas from preterm PET pregnancies compared with those from preterm 'controls'. Interestingly, total macrophage numbers were significantly higher in the PET group and positively correlated with PET severity (Schonkeren et al 2011). However, although this shift towards a pro-inflammatory cytokine environment is described in the context of malplacentation disorders, this is an over-simplification; contradictory information exists as outlined later in this review.…”
Section: Decidual Macrophagesmentioning
confidence: 84%
“…In the context of adverse pregnancy, elevated serum concentrations of IL12 (which augment the production of inflammatory cytokines) have also been measured in the peripheral blood of women with pre-eclampsia (PET) (Saito et al 1999). Lower levels of anti-inflammatory IL10 have also been reported in the decidua basalis in cases of PET (Schonkeren et al 2011, Darby et al 2013. Polarisation towards an M2 macrophage subtype has also been observed in normal-term placentas relative to those from women with pregnancies complicated by both preterm birth and PET.…”
Section: Decidual Macrophagesmentioning
confidence: 99%
“…Most studies have focused on the number of decidual macrophages and these have failed to show consistent results for instance showing both unaltered, decreased and increased numbers of macrophages in preeclamptic patients (Burk et al, 2001;Lockwood et al, 2006;Kim et al, 2007;Schonkeren et al, 2011). Thus, the role of decidual macrophages in the development of complications is likely to be more related to the function of macrophages (or a combination of the both).…”
Section: The Role Of Decidual Macrophages In Pregnancy Complicationsmentioning
confidence: 99%
“…Thus, the role of decidual macrophages in the development of complications is likely to be more related to the function of macrophages (or a combination of the both). Indeed, some studies have reported altered expression of M2 macrophage markers (for instance CD163, CD206 and CD209) (Schonkeren et al, 2011;Hsu et al, 2012;Prins et al, 2012) or production of factors influencing macrophage polarization (for instance GM-CSF and IL-10) (Hennessy et al, 1999;Huang et al, 2010;Schonkeren et al, 2011) in pregnancy complications. However, evidence is still scarce, partly reflecting the limited information about decidual macrophage function during healthy pregnancy.…”
Section: The Role Of Decidual Macrophages In Pregnancy Complicationsmentioning
confidence: 99%